Pirate Radio (Universal, 2009)
The story opens in 1966, aboard a rusty fishing trawler christened Radio Rock and equipped with pirate broadcasting equipment. Here, the slightly daft elitist Quentin (Bill Nighy) presides over a motley crew of joint-toking, sex-hungry disc jockeys including Dave (Nick Frost), a heavyset boob who nevertheless considers himself a hot property with women and loves to chase skirts; "The Count" (Philip Seymour Hoffman), an American DJ who aspires to be the first person to drop an F-bomb over the British airwaves; the gloom-laden Irishman Simon (Chris O'Dowd); bonked-out hipster Thick Kevin (Tom Brooke); womanizer Mark (Tom Wisdom); Angus (Rhys Darby), a New Zealander whom nobody likes; and the only female member of the group, lesbian cook Felicity (Katherine Parkinson). These misfits pull off quite a show -- enough of one that they attain the status of national idols for the youth culture -- but the super-conservative government minister Dormandy (Kenneth Branagh) detests the whole business and will do almost anything in his power to shut them down.
Philip Seymour Hoffman, Bill Nighy, Nick Frost, Chris O'Dowd, Rhys Darby
Keywords: 1960's.; Youth Culture